PENGARUH MUSIK KARYA BACH TERHADAP FUNGSI KOGNISI ATENSI DAN MEMORI JANGKA PENDEK - Yenni Limyati,* Azalia Rahmanita Erman,** Winda Permata Sari,** Johan Lucianus,*** Budi Widyarto Lan (Neurona Majalah Kedokteran Neuro Sains, 2018)
INTRODUCTION A STUDENT WHO HAS A MYRIAD OF ACTIVITIES ON AND OFF CAMPUS BESIDES BEING REQUIRED TO HAVE THE ABILITY TO MANAGE TIME EFFICIENTLY THEY ARE ALSO REQUIRED TO HAVE A GOOD COGNITIVE FUNCTION ESPECIALLY FOR ACADEMIC ACTIVITIES MANY FACTORS CAN INTERFERE WITH LEARNING ACTIVITIES INCLUDING ATTENTION PROBLEMS AND DIFFICULTY REMEMBERING SOME STUDIES SAY THAT BACHS RHYTHMIC AND SOFT MUSIC INFLUENCES THE ABILITY TO ABSORB INFORMATION AND REMEMBER